Bankability of hydrogen projects: Key risks, financing challenges and mitigation solutions - Henry Rushton; Aliaksei Patonia (The Oxford Institute for Energy Studies, 2026)
This paper explores the critical financial challenges in developing and financing hydrogen projects, particularly in the context of their role in achieving global decarbonisation goals. It examines the perspectives of key stakeholders - investors, banks, policymakers, project developers, and off-takers - and identifies the primary risks and corresponding mitigation strategies, with a focus on financing and off-take structures that enhance project bankability. Grounded in project finance theory and current market data, the analysis concludes that while innovative financing models are emerging, the paramount determinant of bankability remains the establishment of robust, long-term off-take contracts that effectively allocate volume and price risk. The study further finds that the role of public policy in bridging the initial cost gap and de-risking investment is indispensable for the sector's scale-up.
Keywords: 330; blue' hydrogen; blended finance; CfDs; Clean hydrogen; Energy Transition; green hydrogen; H2Global; hydrogen bankability; hydrogen offtake; NEOM; policy support; PPAs; project finance; SPAs